Psychological Contract of Buyer-Supplier Relationships in Construction Projects: An Analysis Based on Game Theory - Qi Luo; Kun Lu (Complexity)
Expect for formal contracts, there are informally unwritten psychological contracts (PC) in the relationship between buyer and supplier for construction projects. The PC can affect the construction project performance and even cause project failure, but its process and formation are complex and not comprehensive in existing researches. This paper analyzes the PC between buyer and supplier by using evolutionary game and repeated game to tackle this gap. The results show the following: (1) the goodwill and interest have an important impact on PC fulfillment. (2) The PC is vulnerable; for example, once either one fails to perform PC, the other will also destroy PC, and then the construction project will enter a vicious circle. (3) In the process of repeated game, the effect of goodwill will gradually disappear, and the interest will play a major role. (4) If the project performance is only linked to one participant, it will lead to breach from another player. Some measures may help both sides to complete PC, such as making both sides profitable, increasing the emphasis on business reputation, and improving the relevance of construction projects performance.